Effects of gamma irradiation on growth and productivity in dose-dependent response of Indian mustard (Brassica juncea L.) genotypes - Kumari Aanchal,; Prashant Kumar Rai,; Vaidurya Pratap Sahi,; Shivam Kumar Rai, (Journal of Oilseed Brassica, 2025)
Gamma irradiation is a widely used mutagenic technique in plant breeding, employed to induce genetic variations for crop improvement. In this study, the effects of different doses of gamma irradiation (0, 5, 10, 15, 20 and 25 kR) on the morphological, phenological, yield, and quality traits of two Indian mustard (Brassica juncea L.) genotypes, P13RGN303 and RH-761, were investigated. The study focused on key parameters such as field emergence, survival rate, plant height, days to 50% flowering, siliqua length, siliqua per plant, number of seeds per siliqua, seed yield, test weight and oil content. Significant variations were observed across the different radiation treatments, with the highest performance noted at 20 kR for both genotypes. The optimal doses of gamma irradiation (20 kR) resulted in increased field emergence and survival rates, indicating improved seed vigour. Furthermore, plant height and days to 50% flowering were favorably affected, suggesting enhanced growth and early maturity. Siliqua traits, including siliqua length and seed number, as well as seed yield (per plant, plot, and hectare), were all significantly improved, reflecting increased reproductive efficiency. The highest test weight and oil content were recorded at 20 kR, signaling enhanced seed quality. Conversely, higher doses (25 kR) led to a reduction in growth and yield, likely due to excessive radiation stress. Overall, the study demonstrates the potential of gamma irradiation at 20 kR for improving mustard traits, providing valuable insights for crop improvement initiatives